Analisis Komparatif Pandangan Preteris, Historis, Simbolis, Dan Futuris Terhadap Frasa ”Yerusalem Baru” Dalam Kitab Wahyu 21 - Silalahi, Binsar Pandapotan; Lewi, Jani (Sekolah Tinggi Teologi Injili Indonesia Ambon, 2025)
This study explores the meaning of the phrase “New Jerusalem” in Revelation 21 by conducting a comparative study of four interpretive paradigms, namely preterist, historical, symbolic, and futurist. The phrase “New Jerusalem” tends to be interpreted in various ways, resulting in conceptual gaps regarding this eschatological symbol. This research employs a qualitative method based on literature review, supported by primary sources such as the Greek text NA28 and secondary literature from collections of theological interpretations. In this case, it was found that each interpretation offers a unique theological nuance regarding the eternal existence of God among His people. The findings show that the phrase “New Jerusalem” can not only be understood as a futuristic reality, but also as the theological identity of the present-day church as a holy community that must live in the light of God's glory and the eschatological hope that continues to be proclaimed.